A comparison study on the elements of storytelling between Malaysia and Thailand TV advertisements / Amir Lukman Abd Rahman, Ainal Maziah Salleh and Aini Andria Shirin Anuarudin - Abd Rahman, Amir Lukman; Salleh, Ainal Maziah; Anuarudin, Aini Andria Shirin (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
The application of emotions and dreams portrayed in TV advertisements is appealing to individuals who seek experiences and this has proven to be one of the positive consequences of storytelling in TV advertisements. Television advertising has been influenced by the application of storytelling. This paper explores storytelling as an engaged pedagogy in formal and informal learning. The research approach used was a mixed method. First semiotic qualitative analysis was used to analyse online TV advertisements from Malaysia on Mother’s Day celebration and Thailand’s cultural identity of showing gratitude. Survey questionnaires were also used. Based on Ye, Buettner and Kovashka’s (2018) Storytelling Analysis framework, the findings revealed that storytelling in TV advertisements bring positive effects towards the intended audience, which included individuals seeking experience from stories, stories that turn everyone into heroes and the application of “narrative transportation”. The emotional appeal in both advertisements has also affected the respondents’ thought and views on TV advertisements where 90% of the respondent agreed that both Malaysia and Thailand TV advertisements depicted an emotional effect in terms of sadness. In conclusion, the findings suggest some evidence about the phases of storytelling based on the Storytelling Analysis Framework and the application of emotional effects in both Malaysia and Thailand TV advertisements.